Antidepressent Effect of Two New Benzyl Derivatives from Wild Strawberry Fragaria vesca var. nubicola Lindl. ex Hook.f. - Naz, Sadia; Farooq, Umar; Khan, Ajmal; Khan, Haroon; Karim, Nasiara; Sarwar, Rizwana; Hussain, Javid; Rauf, Abdur (Frontiers in Pharmacology, 2017)
Two new benzyl derivatives were isolated from ethyl acetate fraction of wild strawberry, Fragaria vesca var. nubicola Lindl. ex Hook.f. The structures of these compounds were elucidated to be 5-(4-hydroxy-3-methoxyphenethyl)-7-methoxy-2H-chromen-3-ol (1) and 5-(4-hydroxy-3-methoxyphenethyl)-4,7-dimethoxy-2H-chromen-3-ol (2) based on spectroscopic data through IR, UV, 1H-NMR, 13C-NMR along with two dimensional (2D) techniques HMBC, HMQC, and COSY. Both compounds 1 and 2 were studied in tail suspension and forced swim tests for antidepressant like effects. A significant dose dependent antidepressant like effect was observed by causing spontaneous anti-immobility at various test doses upon intraperitoneal administration.